Design of a Cross-Layer Anti-Jamming Routing Protocol for FANETS Based on Spatial Filtering - Qiong Yu; Cong Wang; Hao Wang; Wenfeng Ma; Hui Tian; Yi Zhu; Ming Lu; Xun Liu; Yuchen Ji; Chengyu Zhang (IEEE Access, 2025)
Flying Ad Hoc Networks (FANETs) are an essential component of future integrated air-space strategic systems. To achieve efficient and reliable network communication between nodes, a routing protocol capable of adapting to dynamic network changes and complex electromagnetic environments is required. This paper explores routing protocols for reliable networking between flight platforms in highly contested environments and the main idea is introducing link quality factors. Based on the integration of link quality for routing establishment, this study further investigates the performance of a cross-layer anti-jamming multi-hop routing protocol based on spatial disturbance resistance capabilities of nodes. It comprehensively evaluates link quality, incorporating nodes’ spatial disturbance resistance capabilities, to identify the most reliable routes in FANETs. Simulation results indicate that when nodes possess certain spatial disturbance resistance capabilities, routing established based on link quality can further ensure the network’s average throughput under interference conditions, as well as maintain a low packet loss rate.